Marketing Strategy Analysis in the Digital Age in Facing Business Competition at Virgin Cake & Bakery Semarang - Frisca Priscillia; Rina Rachmawati (Universitas Negeri Semarang, 2026)
The development of information technology in the digital era has changed the business landscape, encouraging Micro, Small, and Medium Enterprises (MSMEs) to adapt in order to remain competitive. Increasingly fierce competition requires MSME bakeries to comprehensively optimize their digital marketing strategies. This study aims to analyze the digital marketing strategy of Virgin Cake & Bakery Semarang by reviewing five main indicators, namely product superiority, price, location, digital information, and promotion. The research method used is quantitative with a descriptive percentage approach to analyze the perceptions of 100 respondents selected using purposive sampling based on the Lemeshow formula for an infinite population. The research instrument was tested for validity using the Product Moment Pearson formula (r > 0.444) and reliability using the Cronbach's Alpha method (α > 0.60). The data were analyzed using mean and percentage calculations, then interpreted on a five-category interval scale. The results showed that the overall implementation of Virgin Cake & Bakery's digital marketing strategy was in the good category. The product excellence indicator received the highest average score of 4.14, followed by location 4.10, price 4.07, digital information 3.84, and promotion 3.53, which was the lowest score. These findings indicate that although product excellence is a major strength, the aspect of digital promotion still needs to be improved in terms of intensity and creativity. The practical implications of this study provide recommendations for Virgin Cake & Bakery to increase the frequency of promotional content, utilize paid advertising, and collaborate with local influencers to expand market reach and strengthen competitiveness in the digital era.